2002
DOI: 10.1038/sj.bjc.6600007
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and childhood cancer: analysis of individual patient data from six case–control studies

Abstract: To investigate the hypothesis that neonates who receive intramuscular vitamin K are at an increased risk of developing cancer, particularly leukaemia, a pooled analysis of individual patient data from six case -control studies conducted in Great Britain and Germany has been undertaken. Subjects comprised 2431 case children diagnosed with cancer before 15 years of age and 6338 control children. The retrospective assessment of whether or not an individual baby received vitamin K is not straightforward. In many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…administration of vitamin K accords with the majority of individual studies to have reported on this topic (Ekelund et al, 1993;Klebanoff et al, 1993;Olsen et al, 1994;Ansell et al, 1996;von Kries et al, 1996;Roman et al, 1997;McKinney et al, 1998;Passmore et al, 1998a, b) and with the results of an individual record-based pooled analysis of the six major case -control studies (Roman et al, 2002). The one exception is a study carried out in the former Northern Health region of England which, although it found no association for all childhood ALL (OR ¼ 1.20, 95% CI ¼ 0.75 -1.92, based on 207 cases), reported a statistically significantly raised OR for ALL diagnosed between 12 and 71 months of age (OR ¼ 1.79, 95% CI ¼ 1.02 -3.15, based on 144 cases) (Parker et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…administration of vitamin K accords with the majority of individual studies to have reported on this topic (Ekelund et al, 1993;Klebanoff et al, 1993;Olsen et al, 1994;Ansell et al, 1996;von Kries et al, 1996;Roman et al, 1997;McKinney et al, 1998;Passmore et al, 1998a, b) and with the results of an individual record-based pooled analysis of the six major case -control studies (Roman et al, 2002). The one exception is a study carried out in the former Northern Health region of England which, although it found no association for all childhood ALL (OR ¼ 1.20, 95% CI ¼ 0.75 -1.92, based on 207 cases), reported a statistically significantly raised OR for ALL diagnosed between 12 and 71 months of age (OR ¼ 1.79, 95% CI ¼ 1.02 -3.15, based on 144 cases) (Parker et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The one exception is a study carried out in the former Northern Health region of England which, although it found no association for all childhood ALL (OR ¼ 1.20, 95% CI ¼ 0.75 -1.92, based on 207 cases), reported a statistically significantly raised OR for ALL diagnosed between 12 and 71 months of age (OR ¼ 1.79, 95% CI ¼ 1.02 -3.15, based on 144 cases) (Parker et al, 1998). To investigate this further, a metaanalysis of the results published by Roman et al (2002) and the results reported here has been undertaken. In order to do this, the analyses reported here were repeated comparing oral þ given unknown route þ not given þ no record (baseline group) with i.m.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A risk of solid tumours can now almost definitely be ruled out, but a small risk of leukaemia cannot be excluded. [17,35]. When cases of late VKDB started to reappear, Denmark, Canada, Australia and New Zealand responded by reintroducing universal IM prophylaxis, offering oral prophylaxis with repeated doses to those parents refusing the IM injection at birth.…”
Section: Vitamin K Prophylaxis In the Newbornmentioning
confidence: 97%
“…Plasma vitamin K 1 in VLBW was very high at 1 week of age compared to earlier studies in healthy newborns (Shearer et al, 1982;Greer et al, 1988) and in preterm infants (Kumar et al, 2001;Costakos et al, 2003). Several authors, although not confirmed in randomized studies, have suggested deleterious side effects from high vitamin K levels such as childhood leukemia and hepatoblastoma (Roman et al, 2002). At present, it is not known whether high plasma vitamin K concentration in the neonatal period increases disease risks.…”
Section: Fat-soluble Vitaminsmentioning
confidence: 90%